Search for the Standard Model Higgs boson decay to mu(+)mu(-) with the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Khalek, SA; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; Abreu, R; et al. (2014)
A search is reported for Higgs boson decay to μ+μ-using data with an integrated luminosity of 24.8fb-1collected with the ATLAS detector in ppcollisions at √s=7 and8TeVat the CERN Large Hadron Collider. The observed dimuon invariant mass distribution is consistent with the Standard Model background-only hypothesis in the 120-150GeV search range. For a Higgs boson with a mass of 125.5GeV, the observed (expected) upper limit at the 95% confidence level is 7.0 (7.2) times the Standard Model expectation. This corresponds to an upper limit on the branching ratio BR(H→μ+μ-)of 1.5 × 10-3.